Backstaging the teacher: On learner-driven, school-driven and data-driven change in educational technology discourse - Macgilchrist, Felicitas (Kultura-Społeczeństwo-Edukacja, 2019)
As digital technologies become more prominent in schools, and a host of new media products appear in classrooms, critical questions are being asked about the erasure of power and politics in contemporary education. To explore the discourse on digital education, this paper draws on discourse analysis of ethnographic interviews with for-profit and non-profit organizations in the field. It asks (i) what industry insiders describe as driving change in contemporary educational technology (edtech), and (ii) whether new actors/technologies shaping a novel educational hegemony, and if so, what this hegemony looks like. Initial findings suggest that while the teacher was seen as key to driving change in printed educational materials, three different discourses appear when describing change in today’s educational technology. In the first, learners drive change; the focus lies on the individual dimension. In the second, schools drive change; the systemic dimension. In the third, data drive change; the analytics dimension. Linking these three discourses is a shift from “education” to “learning”. The accounts of educational technology simultaneously advocate for improving opportunities for all students, especially weaker or disadvantaged learners, and also strengthen the hegemonic shift across policy and practice towards an instrumental understanding of education. Overall, the paper suggests that power and politics are by no means erased from the edtech industry’s accounts of digital technologies and datafication. The socio-material affordances engineered into the technologies invite particular teaching practices and thus affect power relations in education.